Vocabulary Acquisition in EFL: A Literature Review of Innovative Vocabulary Teaching Strategies - Sutrisna, Gede (Institut Hindu Dharma Negeri Denpasar, 2021)
In language learning, it is important for teachers to have in-depth consideration on the strategy of teaching vocabulary. It is advised to choose a strategy which brings lots of benefits for students’ vocabulary acquisition. The strategy not only should facilitate the students to achieve the learning objectives, but also provide them with enjoyable and meaningful activities. It must be able to challenge the students so that they can actively and creatively participate during vocabulary teaching learning process. When they are involved, they are receiving, understanding and using the material given. Those processes will effectively promote their comprehension and vocabulary development. The purpose of this paper is to explore three innovative strategies for teaching vocabulary: Flip-a-Chip, Word Ladders and The Ripple Effect.